Leader behavior and teacher perceptions of organizational climate in public primary schools in Melbourne, Australia. - Maddern, Dennis James (My University, 1980)
These findings were similar to other leader behavior--organizational climate studies in other countries which gives further evidence to these instruments in terms of validity and reliability. It further indicates that organizational climate as measured by the OCDQ is being, and can be manipulated by certain variables associated with a leader's behavior.

The independent variable was leader behavior, which was measured by the sub-tests of the Leader Behavior Description Questionnaire (LBDQ) i.e., Initiating Structure and Consideration. The dependent variable was organizational climate which was measured by the salient sub-tests of the Organizational Climate Description Questionnaire (OCDQ) i.e., Thrust, Esprit and Consideration.

This study was designed to determine whether a relationship exists between leader behavior and organizational climate. The study was conducted in 47 primary schools in Melbourne, Australia.

Canonical correlation analysis along with the Pearson Moment Product Correlation was utilized as the statistical methodology. The data analysis showed that a statistically significant relationship existed between H(, 2); Initiating Structure - Thrust, H(, 4); Consideration LBDQ - Consideration OCDQ, H(, 5); Consideration - Thrust, H(, 6); Consideration - Esprit. H(, 1) Initiating Structure - Consideration and H(, 3) Initiating Structure - Thrust were found not be statistically significant.
Keywords: Education, Administration.